Waste Segregation Management Using Object Sorting Robot - Lokesh, S.; Kiran, S.; Vijay, B.; B. Yuvaraaj, S.; Yuvaraj, S. (International Journal of Engineering and Technology, 2018)
Every year our world are facing a huge issue in the area waste goods management. The proposed system designed as an automated   sorting of waste segregation management based on object recognition. sorting of different objects on a conveyor belt is generally carried out manually or by using sensors. In this paper we have proposed a low cost automated system which uses Arduino, moisture sensor, ultrasonic sensor, IR sensor, metal detector and a USB camera. We use Camera for detecting the object and the four different sensors are used for the sensing purposes. In addition to that a ultrasonic sensor for distance measurements and dc motor for conveyor belt applications and for sorting purpose. The system discard the objects which are not of desired object or size by pushing them out of the conveyor belt.